Filosofskaja enciklopedija. Gl. red.: F.V. Konstantinov, Čl. red. koll.: V.F. Asmus, L.F. Denisova i dr ("Sovetskaja Enciklopedija")
In-t filosofii AN SSSR. Gos. naučnoe izd-vo: "Sovetskaja enciklopedija"